2022
DOI: 10.3390/en15093419
|View full text |Cite
|
Sign up to set email alerts
|

Briquettes from Pinus spp. Residues: Energy Savings and Emissions Mitigation in the Rural Sector

Abstract: This study analyzes the household energy needs of the indigenous community of San Francisco Pichátaro, Michoacán, Mexico, and the use of Pinus spp. wood residues for the production of briquettes. The energy and emission performances of wood briquettes were evaluated on the field and in the laboratory. On-field surveys and measurements show that most users combine the use of fuelwood and LPG for cooking and heating water, and 65% of people use fuelwood daily (40% of houses consumed more than 39 kg per week). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…Other studies compare the environmental impact of biomass briquettes in comparison to fossil energy [15]. Biomass briquette is found to be more economically viable and able to reduce CO2 emissions [5]. The study conducted by Sulaiman [16] on 27 European Union (EU) countries, reinforces this finding by emphasizing that biomass energy can reduce CO2 emissions better than fossil energy.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Other studies compare the environmental impact of biomass briquettes in comparison to fossil energy [15]. Biomass briquette is found to be more economically viable and able to reduce CO2 emissions [5]. The study conducted by Sulaiman [16] on 27 European Union (EU) countries, reinforces this finding by emphasizing that biomass energy can reduce CO2 emissions better than fossil energy.…”
Section: Introductionmentioning
confidence: 87%
“…Studies demonstrate that combustion properties increase by 20% after biomass is compacted into solid briquettes, resulting in lower emissions than coal. Utilizing renewable energy from biomass is a cost-effective technology that can reduce CO2 emissions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Biomass briquettes have a lower carbon footprint and surpass alternative cooking fuels such as wood in heat output per unit mass, moisture content, and storage space. Just like Bonsu et al [67] observed, appropriate briquette use would help mitigate climate change impacts by reducing the over-reliance on wood for household and commercial heating.…”
Section: Sawdust Briquettesmentioning
confidence: 93%
“…The main energy used in urban areas is natural gas and electricity, while most rural residents still use many traditional biomass fuels, such as stalks and firewood, in their daily lives [45,46]. Natural gas is uncommon in rural areas [38].…”
Section: Energy Structurementioning
confidence: 99%